2022
DOI: 10.3389/fgene.2022.833923
|View full text |Cite
|
Sign up to set email alerts
|

F2RL3 Methylation in the Peripheral Blood as a Potential Marker for the Detection of Coronary Heart Disease: A Case-Control Study

Abstract: Background and Aims: Previous work has shown the association between blood-based methylation of coagulation factor II receptor-like 3 gene (F2RL3) and cardiovascular mortality in Caucasians. However, the diagnostic value of F2RL3 methylation for CHD is still unknown. The aim of our study was to evaluate the association between blood-based F2RL3 methylation and the risk of CHD in the Chinese population.Methods: The methylation level of F2RL3 was quantified by mass spectrometry in a case-control study with 180 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…A total of 1452 CpG sites were mentioned once or more in at least two of the publications, 441 CpG sites were mentioned once or more in at least three publications, and two CpG sites were mentioned in ≥ 6 publications (Table 2 ). The two latter CpG sites are cg01656216 near gene ZNF438 (mentioned in [ 10 , 22 , 30 , 60 , 65 , 108 ]) and cg03636183 near gene F2RL3 (mentioned in [ 49 , 69 , 75 , 79 , 113 ], Table 3 ). These two CpG sites are also part of the methylation clocks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1452 CpG sites were mentioned once or more in at least two of the publications, 441 CpG sites were mentioned once or more in at least three publications, and two CpG sites were mentioned in ≥ 6 publications (Table 2 ). The two latter CpG sites are cg01656216 near gene ZNF438 (mentioned in [ 10 , 22 , 30 , 60 , 65 , 108 ]) and cg03636183 near gene F2RL3 (mentioned in [ 49 , 69 , 75 , 79 , 113 ], Table 3 ). These two CpG sites are also part of the methylation clocks.…”
Section: Resultsmentioning
confidence: 99%
“…Three out of six papers mentioning cg01656216 [ 22 , 30 , 108 ] have vascular disease as an outcome, whereas the three other publications had investigated epigenetic age [ 10 , 60 , 65 ]. In the case of cg03636183, three out of six publications had coronary heart disease or myocardial infarction as the outcome [ 75 , 79 , 113 ], and the other three had investigated smoking or air pollution [ 12 , 49 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…This investigation is based on a case–control study, details of which have been reported elsewhere [ 37 ]. Briefly, 180 patients with CHD and 184 controls were collected from the Chinese PLA General Hospital from 2018 to 2019.…”
Section: Methodsmentioning
confidence: 99%
“…[8] F2RL3 gene has been shown to play a key role in mediating platelet activation, as well as a variety of signaling pathways, such as immune response, regulation of vascular endothelial cell activity, and inflammatory response. [9] Relevant studies have shown that epigenetic regulation of F2RL3 may increase platelet reactivity through protease activates receptor 4 function, thereby increasing the risk of morbidity and mortality of myocardial infarction. [10]…”
Section: Introductionmentioning
confidence: 99%
“…[8] F2RL3 gene has been shown to play a key role in mediating platelet activation, as well as a variety of signaling pathways, such as immune response, regulation of vascular endothelial cell activity, and inflammatory response. [9] Relevant studies have Written informed consent was obtained from all patients.…”
Section: Introductionmentioning
confidence: 99%